The Development of Project-Based Learning Models That Accommodate the Reflective and Impulsive Cognitive Style - Imas Cintamulya; Warli; Lilik Mawartiningsih (Indonesia Approach Education, 2024)
Ideally, a teacher must choose a learning model, approach, method, or technique that suits the student's learning style. This research describes the design of a project-based learning (PjBL) model that accommodates reflective and impulsive cognitive styles. For this reason, development research was carried out using the Plomp model. To determine the quality of the results of PjBL development that accommodates reflective and impulsive cognitive styles, validity, practicality, and effectiveness tests were carried out. Based on the results of the validity test analysis, it was concluded that content validity was very good, while construct validity was good. The results of the practicality test concluded that the syntax and social system were declared good, while the reaction and management principles were declared very good. For the effectiveness test results, it was concluded that teacher and student activities were good, learning management abilities were stated to be very good, student responses to learning components and processes were stated to be good, and learning outcome tests were also good. Overall, it can be concluded that the PjBL model, which accommodates reflective and impulsive cognitive styles, is good and suitable for use. The research results imply that this model can be used as a choice for teachers in learning.